The formation mechanism of acute dissection of blood blister-like aneurysm and its implication of endovascular treatment - Ye, Zhongyin (Chin Neurosurg J, 2021)
BACKGROUND: Acute mural dissection of the anterior wall of the internal carotid artery which may contribute to the development of blood blister-like aneurysms (BBLAs) was postulated, and stenting or flow diversion treatment across the soi-disant aneurysm was reported in this study. METHODS: From December 2016 to December 2018, 8 patients presenting with subarachnoid hemorrhage (SAH) due to BBLA were subjected to endovascular treatment with stent-assisted coiling. Clinical outcomes were evaluated using a clinical outcome score scale. RESULTS: Based on angiograms, pathologic change involving the supraclinoid segments of the internal carotid artery (ICA) adjacent to BBLA was found in all patients. This pathologic change meant a focal dissection of the supraclinoid segment of the ICA which constituted the pathogenesis of BBLAs. Closed-cell, open-cell, and braided stents were used in 1, 1, and 6 patients, respectively. Complete obliteration was achieved following endovascular treatment among all 8 patients harboring BBLA. One re-bleeding successive to a closed-cell stent across the aneurysmal neck was observed. Follow-up angiograms revealed stable complete exclusion of all BBLAs from the parent vessel at 3 to 8 months. All patients had a favorable clinical outcome score of 0–1. CONCLUSIONS: Acute dissection of a focal point of the intracranial vessels underlies the development of BBLAs. Open-cell and braided-cell stent-assisted coiling may constitute appropriate treatment due to good apposition against the vascular walls. Adjunctive coils may facilitate immediate complete occlusion of BBLAs.